1991
DOI: 10.1037/0021-843x.100.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Bias in interpretation of ambiguous sentences related to threat in anxiety.

Abstract: In the 1st of 2 experiments, currently clinically anxious, recovered clinically anxious, and normal control subjects were presented with a mixture of unambiguous and ambiguous sentences; both threatening and nonthreatening interpretations were possible for the latter. A subsequent recognition-memory test indicated that the currently anxious subjects were more likely than normal control and recovered anxious subjects to interpret the ambiguous sentences in a threatening fashion rather than in a nonthreatening f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
276
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(298 citation statements)
references
References 16 publications
18
276
2
2
Order By: Relevance
“…Scores on the BDI are highly correlated with trait anxiety measures. Plainly, anxiety experienced by our dysphoric participants might be at least partly responsible for the pattern of results, because interpretive biases have frequently been demon strated in anxiety (e.g., Eysenck, Mogg, May, Richards, & Mathews, 1991;MacLeod & Cohen, 1993). Recently, anxiety-related interpretive biases have been successfully modeled in nonanxious groups (e.g., Mathews & Mackinto sh, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…Scores on the BDI are highly correlated with trait anxiety measures. Plainly, anxiety experienced by our dysphoric participants might be at least partly responsible for the pattern of results, because interpretive biases have frequently been demon strated in anxiety (e.g., Eysenck, Mogg, May, Richards, & Mathews, 1991;MacLeod & Cohen, 1993). Recently, anxiety-related interpretive biases have been successfully modeled in nonanxious groups (e.g., Mathews & Mackinto sh, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…Previous research has shown that anxious individuals have a tendency to interpret ambiguous information as negative (Eysenck, Mogg, May, Richards, & Mathews, 1991;MacLeod & Cohen, 1993;Bar-Haim et al, 2007) and the presentation of the social threat word may increase this propensity. This could explain the lack of change in the ERPs of high socially-anxious individuals between threat prime trials and neutral prime trials.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, there is extensive evidence that anxious typically-developing individuals are biased to interpret ambiguous stimuli as threatening (Creswell et al, 2005;Eysenck et al, 1991;Hadwin et al, Interpretation bias 17 1997;Muris et al, 2003). Given the interpretation bias evident for the WS group on the physical situations, the present findings suggest that the cognitive processes underpinning GAD and Specific Phobia in this atypical population may be similar to those that underpin anxiety in the typically developing population.…”
Section: Implications For Treatment Of Anxiety In Wsmentioning
confidence: 47%
“…In contrast, a non-threatening interpretation would be that someone dropped something. There is substantial evidence, based on research using both methodologies, that clinically anxious adults and children, and individuals high in trait anxiety, exhibit a tendency to interpret ambiguous stimuli in a threatening way (Creswell, Schniering, & Rapee, 2005;Eysenck et al, 1991;Hadwin, Frost, French, & Richards, 1997;Muris, Rapee, Meesters, Shouten, & Geers, 2003). In one such study, Barrett, Rapee, Dadds, and Ryan (1996) asked clinically anxious and non-anxious control children what they would think was happening in twelve ambiguous situations.…”
Section: Interpretation Biasmentioning
confidence: 99%